2022
DOI: 10.3390/polym14030495
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Azithromycin Amorphous Solid Dispersion by Hot-Melt Extrusion: An Advantageous Technology with Taste Masking and Solubilization Effects

Abstract: Azithromycin (AZI) is one of the most commonly used macrolide antibiotics in children, but has the disadvantages of a heavy bitter taste and poor solubility. In order to solve these problems, hot-melt extrusion (HME) was used to prepare azithromycin amorphous solid dispersion. Preliminary selection of a polymer for HME was conducted by calculating Hansen solubility parameter to predict the miscibility of the drug and polymer. Eudragit® RL PO was chosen as the polymer due to its combination of taste-masking eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…The most important characteristics of the vibration bands for azithromycin, in accordance with the literature [ 44 , 45 , 46 ], are as follows: 3558 and 3485 cm −1 (O-H); 2971 and 2783 cm −1 (C-H); 1720 cm −1 (-C=O); 1638 cm −1 , 1458 cm −1 , 1378 cm −1 , 1343 cm −1 , 1281 cm −1 , and 1185 cm −1 (-C-O); 1082 cm −1 and 1051 cm −1 (R-O-R and C-N), 995 cm −1 , 900 cm −1 , 834 cm −1 , 795 cm −1 , and 730 cm −1 (C-H), 639 cm −1 and 573 cm −1 .…”
Section: Resultssupporting
confidence: 84%
“…The most important characteristics of the vibration bands for azithromycin, in accordance with the literature [ 44 , 45 , 46 ], are as follows: 3558 and 3485 cm −1 (O-H); 2971 and 2783 cm −1 (C-H); 1720 cm −1 (-C=O); 1638 cm −1 , 1458 cm −1 , 1378 cm −1 , 1343 cm −1 , 1281 cm −1 , and 1185 cm −1 (-C-O); 1082 cm −1 and 1051 cm −1 (R-O-R and C-N), 995 cm −1 , 900 cm −1 , 834 cm −1 , 795 cm −1 , and 730 cm −1 (C-H), 639 cm −1 and 573 cm −1 .…”
Section: Resultssupporting
confidence: 84%
“…These particles have been observed to possess great potential for in vivo applications. Chang et al observed that the hydrophobic encapsulation of cur-cumin in egg white protein nanoparticles was enhanced, thus effectively decreasing its degradation rate and safeguarding its antioxidant activity when compared to nonencapsulated particles [97][98][99] .…”
Section: B) Peptide Complexationmentioning
confidence: 99%
“…With this variety of methods you will be able to ensure optimal performance in your drug application. The solubility of any drug is heavily determined by the chemical make-up and the components of its solution [18][19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…In TSMG, the process is carried at a temperature greater than the melting point of the binder, whereas in TSWG, the process is carried at a temperature below the melting point or the glass transition of the binder. In the TSWG process, the binder solution is sprayed onto the processing material using an external peristaltic pump [48][49][50][51][52][53]. The process's scaleup remains simple since the small-scale extruder employed for early development studies can also be utilized to manufacture commercial products by increasing the processing time.…”
Section: Hot Melt Extrusionmentioning
confidence: 99%